Validation of Geriatric Care Environment Scale in Portuguese Nurses. (28th May 2013) - Paulo de Almeida Tavares, João; Leite da Silva, Alcione; Sá-Couto, Pedro; Boltz, Marie; Capezuti, Elizabeth
Abstract : The number of hospitalized older adults in Portugal necessitates a better understanding of the acute care environment for older adults. This study translated and examined the psychometric qualities of the Geriatric Care Environment Scale (GCES) among 1, 068 Portuguese registered nurses (RNs). Four factors emerged from the exploratory factor analyses: resource availability, aging-sensitive care delivery, institutional values regarding older adults and staff, and continuity of care. The internal consistency of the GCES was α = .919 . The GCES was significantly associated with the variables of region, hospital type, unit type, and RNs perception of hospital educational, staff knowledge, difficulty, rewarding, and burdensome in caring for older adults. Nurses who worked in hospitals centers in the northern region and medical and surgery units had more positive perceptions of the geriatric care environment. More positive perception was also found among RNs that reported more educational support, had more knowledge, and felt more rewarding and less difficulty and burden in caring older adults. This process resulted in a valid and reliable measurement of the geriatric care environment Portuguese version which provides hospital leadership with an instrument to evaluate organizational support for geriatric nursing practice and target specific areas that support or hinder care delivery.